Finnish teacher-students’ views on home-school cooperation - Perälä-Littunen, Satu; Leena Böök, Marja (International Journal about Parents in Education, 2023)
This study focused on the views on home-school cooperation of teacher-students who are in the process of becoming professionals. The data were gathered from five focus-group interviews of 19 Finnish teacher-students. The data were analysed thematically. Better learning results were not the general aim of cooperation; instead, the aim was the child’s well-being. All parties benefited when cooperation functioned well. Yet, factors related to parents and teachers’ lack of time hinder cooperation. The views of home-school cooperation were a combination of the participants’ childhood memories, stories they had heard from their friends and colleagues and, less saliently, ideas originating from teacher education.